Theranostic potential of self-luminescent branched polyethyleneimine-coated superparamagnetic iron oxide nanoparticles - Khodadust, Rouhollah; Unal, Ozlem; Yagci Acar, Havva (Beilstein Journal of Nanotechnology, 2022)
Polyethylenimine (PEI), which is frequently used for polyplex formation and effective gene transfection, is rarely recognized as a luminescent polymer. Therefore, it is usually tagged with an organic fluorophore to be optically tracked. Recently, we developed branched PEI (bPEI) superparamagnetic iron oxide nanoparticles (SPION@bPEI) with blue luminescence 1200 times stronger than that of bPEI without a traditional fluorophore, due to partial PEI oxidation during the synthesis. Here, we demonstrate in vitro dye-free optical imaging and successful gene transfection with luminescent SPION@bPEI, which was further modified for receptor-mediated delivery of the cargo selectively to cancer cell lines overexpressing the epidermal growth factor receptor (EGFR). Pro-apoptotic polyinosinic–polycytidylic acid sodium (PIC) was delivered to HeLa cells with SPION@bPEI and caused a dramatic reduction in the cell viability at otherwise non-toxic nanoparticle concentrations, proving that bPEI coating is still an effective component for the delivery of an anionic cargo. Besides, a strong intracellular optical signal supports the optically traceable nature of these nanoparticles. SPION@bPEI nanoparticles were further conjugated with Erbitux (Erb), which is an anti-EGFR antibody for targeting EGFR-overexpressing cancer cell lines. SPION@bPEI-Erb was used for the delivery of a GFP plasmid wherein the transfection was confirmed by the luminescence of the expressed gene within the transfected cells. Poor GFP expression in MCF7, a slightly better expression in HeLa, and a significant enhancement in the transfection of HCT116 cells proved a selective uptake and hence the targeting ability of Erb-tagged nanoparticles. Altogether, this study proves luminescent, cationic, and small SPION@bPEI nanoparticles as strong candidates for imaging and gene therapy.
Keywords: Erbitux; photoluminescence; polyethyleneimine; polyinosinic–polycytidylic acid sodium; superparamagnetic iron oxide nanoparticles